Energy levels for growing and finishing steers - K. Bolsen; Michael E. Dikeman; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1976)
Four combinations of low (LE), moderate (ME) and high (HE) energy rations were fed to growing and finishing steers. The four treatments were: LE-ME; LE-HE; ME-ME and ME-HE. All steers were more efficient during the growing phase (473 to 750 lbs.) than the finishing phase (750 to 1050 lbs.). During the growing phase, performance of steers fed the ME ration exceeded that of steers fed the LE ration. During the finishing phase, performance of steers fed the HE ration exceeded that of steers fed the ME ration. Steers on the LE-HE treatment required more energy per lb. of gain than steers on any of the other three treatments. Carcass merit was similar for carcasses from the different treatments. The fact that these cattle were slaughtered at similar weights, and that steers on lower energy rations were fed longer, affected carcass traits more than ration energy did.
Keywords: Cattlemen& #x27; s Day; 1976; Report of progress (Kansas State University. Agricultural Experiment Station); 262; Beef; Energy; Steers; Rations